Improved Cancer Therapy and Molecular Imaging with Multivalent, Multispecific Antibodies - Sharkey, Robert M. (Mary Ann Liebert, Inc., 2010)
Antibodies are highly versatile proteins with the ability to be used to target diverse compounds, such as radionuclides for imaging and therapy, or drugs and toxins for therapy, but also can be used unconjugated to elicit therapeutically beneficial responses, usually with minimal toxicity. This update describes a new procedure for forming multivalent and/or multispecific proteins, known as the dock-and-lock (DNL) technique. Developed as a procedure for preparing bispecific antibodies capable of binding divalently to a tumor antigen and monovalently to a radiolabeled hapten-peptide for pretargeted imaging and therapy, this methodology has the flexibility to create a number of other biologic agents of therapeutic interest. A variety of constructs, based on anti-CD20 and CD22 antibodies, have been made, with results showing that multispecific antibodies have very different properties from the respective parental monospecific antibodies. The technique is not restricted to antibody combination, but other biologics, such as interferon-α2b, have been prepared. These types of constructs not only allow small biologics to be sustained in the blood longer, but also to be selectively targeted. Thus, DNL technology is a highly flexible platform that can be used to prepare many different types of agents that could further improve cancer detection and therapy.